Co-chaperones TIMP2 and AHA1 Competitively Regulate Extracellular HSP90:Client MMP2 Activity and Matrix Proteolysis - Baker-Williams AJ; Hashmi F; Nski MAB; Woodford MR; Gleicher S; Himanen SV; Makedon AM; Friedman D; Cortes S; Namek S; Stetler-Stevenson WG; Bratslavsky G; et al. (CELL PRESS, 2022)
The extracellular molecular chaperone heat shock protein 90 (eHSP90) stabilizes protease client the matrix metalloproteinase 2 (MMP2), leading to tumor cell invasion. Although co-chaperones are critical modulators of intracellular HSP90:client function, how the eHSP90: MMP2 complex is regulated remains speculative. Here, we report that the tissue inhibitor of metalloproteinases-2 (TIMP2) is a stress-inducible extracellular co-chaperone that binds to eHSP90, increases eHSP90 binding to ATP, and inhibits its ATPase activity. In addition to disrupting the eHSP90:MMP2 complex and terminally inactivating MMP2, TIMP2 loads the client to eHSP90, keeping the protease in a transient inhibitory state. Secreted activating co-chaperone AHA1 displaces TIMP2 from the complex, providing a "reactivating'' mechanism for MMP2. Gene knockout or blocking antibodies targeting TIMP2 and AHA1 released by HT1080 cancer cells modify their gelatinolytic activity. Our data suggest that TIMP2 and AHA1 co-chaperones function as a molecular switch that determines the inhibition and reactivation of the eHSP90 client protein MMP2.